A Lei de Diretrizes e Bases da Educação, o neoliberalismo e o ensino profissionalizante no Brasil, a partir da década de 1990 - Resende, Jacione Aparecida Cabral (2020)
This paper analyzes the influence of neoliberal ideas and politics in the Brazilian educational field and the paths taken by civil society and its representatives, mainly the industrial business community, which, with the support of international financing agencies, endeavored to discuss, elaborate and approve a new educational guideline for the country. This process of discussion and elaboration started in the late 1980s dragged on until 1996, when the Fernando Henrique Cardoso government (1995-1998) approved the Law of Education Guidelines and Bases (LDB), nº9394 / 96. Its elaboration process was marked by demands from the industrial area that, through their speech, affirmed the need for a qualified workforce that would meet the technological changes that were arriving in the country at the end of the 20th century. Therefore, it would be from an educational reform, through the approval of a new LDB, the solution found, according to the dominant groups, so that the country could achieve a supposed economic autonomy. Education created as a marketing alternative went through new discussions and drafting of new laws that transformed the way of thinking about professional education with the new LDB.